Polycomb subunits Ezh1 and Ezh2 regulate the Merkel cell differentiation program in skin stem cells. (14th May 2013) - Bardot, Evan S; Valdes, Victor J; Zhang, Jisheng; Perdigoto, Carolina N; Nicolis, Silvia; Hearn, Stephen A; Silva, Jose M; Ezhkova, Elena
<x xml:space="preserve">Abstract</x> While the Polycomb complex is known to regulate cell identity in ES cells, its role in controlling tissue‐specific stem cells is not well understood. Here we show that removal of Ezh1 and Ezh2, key Polycomb subunits, from mouse skin results in a marked change in fate determination in epidermal progenitor cells, leading to an increase in the number of lineage‐committed Merkel cells, a specialized subtype of skin cells involved in mechanotransduction. By dissecting the genetic mechanism, we showed that the Polycomb complex restricts differentiation of epidermal progenitor cells by repressing the transcription factor Sox2. Ablation of Sox2 results in a dramatic loss of Merkel cells, indicating that Sox2 is a critical regulator of Merkel cell specification. We show that Sox2 directly activates Atoh1, the obligate regulator of Merkel cell differentiation. Concordantly, ablation of Sox2 attenuated the Ezh1/2‐null phenotype, confirming the importance of Polycomb‐mediated repression of Sox2 in maintaining the epidermal progenitor cell state. Together, these findings define a novel regulatory network by which the Polycomb complex maintains the progenitor cell state and governs differentiation in vivo.